Potential therapeutic effects of Chinese meteria medica in mitigating drug-induced acute kidney injury - Jun Li; Tonglu Li; Zongping Li; Zhiyong Song; Xuezhong Gong (Frontiers Media S.A., 2023)
Drug-induced acute kidney injury (DI-AKI) is one of the leading causes of kidney injury, is associated with high mortality and morbidity, and limits the clinical use of certain therapeutic or diagnostic agents, such as antineoplastic drugs, antibiotics, immunosuppressants, non-steroidal anti-inflammatory drugs, and contrast media. In recent years, numerous studies have shown that many Chinese meteria medica, metabolites derived from botanical drugs, and Chinese medicinal formulas confer protective effects against DI-AKI by targeting a variety of cellular or molecular mechanisms, such as oxidative stress, inflammatory, cell necrosis, apoptosis, and autophagy. This review summarizes the research status of common DI-AKI with Chinese meteria medica interventions, including cisplatin, gentamicin, contrast agents, methotrexate, and acetaminophen. At the same time, this review introduces the metabolites with application prospects represented by ginseng saponins, tetramethylpyrazine, panax notoginseng saponins, and curcumin. Overall, this review provides a reference for the development of promising nephroprotectants.